Oral trials in the Mexican Constitution - Rueda-Hernández, Gustavo (Universidad Autónoma de Tamaulipas, 2009)
The trials begin in the Constitution of the United Mexican States, the nineteenth day of June two thousand eight, have been reformed under various articles of the penal system with integrated, but the new model of criminal procedure system, enter into force when it set the corresponding secondary legislation, within a period of eight years, counted from the date mentioned above.